Recovery of athletes with visual impairments through modern aspects of physical rehabilitation - Shkola, O.; Kravchenko, I.; Repko, I.; Broslavska, H.; Denysovets, T.; Heitenko, V.; Saiko, N.; Svertnev, O.; Kvak, O.; Hohots, V. (International Journal of Applied Exercise Physiology, 2020)
The article hasdetermined the inseparability of rehabilitation support from sports activities. This was achieved as a result of theoretical analysis of modern approaches to the training process of visually impaired people. Which actualizes the consideration of key theoretical provisions of the modern system of training athletes. It was investigated that the basis of formation of readiness of sportsmen for competitive activity is intellectual development, emotional maturity and socialization. It was found out that along with the development of the ability to maximize physical capabilities, it is necessary to improve the mechanisms of preparation for competitions for visually impaired athletes. This was formed in the aggregate of their technical and tactical, functional andpsychological preparedness.